Specific enlargement of the fourth ventricle after ventriculo-peritoneal shunt for post-haemorrhagic hydrocephalus. Issue 10 (October 1987) - O'Hare, A E; Brown, J K; Minns, R A
Abstract : Disproportionate enlargement or isolation of the fourth ventricle are rare complications of ventriculo-peritoneal shunt for post-haemorrhagic hydrocephalus. Obvious features such as ataxia may indicate raised intracranial pressure in the posterior fossa. The child may, however, present with less specific signs of vomiting, anorexia, and lethargy and these symptoms may be misinterpreted as secondary to dilation of the lateral ventricular system due to malfunction of the ventriculo-peritoneal shunt. Two children with disproportionate enlargement of the fourth ventricle and two children with isolation of the fourth ventricle are described to illustrate the wide variations in clinical presentation. These rare complications can be diagnosed by real time ultrasound examination of the brain or computed tomography of the head. They should be considered in the differential diagnosis of a child who deteriorates after lateral ventriculo-peritoneal shunting for post-haemorrhagic hydrocephalus, and dealt with specifically to avoid the risk of upward herniation of the enlarged fourth ventricle.